An efficacy of protection the organs at risks comparison between the intensitymodulated radiotherapy therapy (IMRT) and the three-dimensional conformal radiotherapy (3DCRT) - Abd Al-Taj Abd Ali Khaleel,; Siham Sabah Abdullah,; Sabbar Shukri Al-Bayaty,; Abdulrahman Mohammed Abdulbaqi,; Nabaa Mohammad Ali Alazawy, (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the efficiency of three-dimensional conformal radiotherapy and intensity-modulated radiation therapy techniques. Method: The cross-sectional study was conducted from February to August 2021 at Al-Amal National Hospital, Baghdad, Iraq, and comprised patients aged 19-45 years with cancerous head and neck tumours of size 2-7cm. All the patients underwent magnetic resonance imaging or computed tomography simulation scans. Treatment planning techniques used for each patient were three-dimensional conformal radiotherapy and intensity-modulated radiotherapy. After evaluating patterns, a better plan and treatment with an X-ray beam was chosen. Data was analysed using SPSS 24. Results: The study involved thirty participants, with 17(57%) females and 13(43%) males, aged 19-45, and 28 patients having chemotherapy. Six out of thirty had craniotomy surgery. The intensity-modulated radiation therapy had a safer radiation dose than the three-dimensional conformal radiotherapy for spinal cord (p=0.3203), brain stem (p= 0.17924), right parotid gland (p=0.8556) and left parotid gland (p=0.2193). The three-dimensional conformal radiotherapy protected the organs better than intensity-modulated radiation therapy for left optic nerve (p=0.1227), right optic nerve (p=0.0032), left eye (p=0.3859), right eye (p=0.1189), left lens (p=0.0004), right lens (p=0.0001), optic chiasm (p=0.0320) and pituitary gland (p=0.9162). Conclusion: The intensity-modulated radiation therapy technique protected the spinal cord, brain stem, and right and left parotid glands. The three-dimensional conformal radiotherapy was safe for left and right optic nerves, left and right eyes, left and right lenses, optic chiasm and pituitary glands. Key Words: Radiotherapy, Parotid Gland, Optic Chiasm, X-Rays, Pituitary Gland, Radiation, Spinal Cord, Brain Stem, Craniotomy, Tomography